A post-adoption framework for Malaysia open government data / Mimi Nurakmal Mustapa - Mimi Nurakmal, Mustapa (2021)
Today, the call for greater transparency from the public administration is progressively apparent. Publishing non-confidential government data to the public is one of the initiatives adopted by many governments today to embrace transparency practice. The initiative of publishing non-confidential government data and accessible by the public for limitless re-use is known as Open Government Data (OGD). The Malaysian government adopted OGD innovation in 2014 and since established a centralised government open data portal. However, after several years of adoption, OGD implementation among government agencies remains unclear. Furthermore, the extant literature on OGD adoption largely focused on the factors that influence OGD adopters’ decisions, whereas the actual use of OGD is more critical. The underlying factors of keeping the adopter continuing or discontinuing OGD implementation in the post-adoption phase are unexplored. Moreover, taking from previous experience, many government innovations were hampered in an inertia state after the adoption phase. Driven from these issues, this study explored the OGD adoption phases and identified the OGD post-adoption factors in the Malaysian public sector. With the stance that the phenomenon can be measured, the positivism philosophy is also applied for this study. Anchored by the Diffusion of Innovation (DOI) theory, Technology-Organisation-Environment (TOE) framework, and innovation adoption process theory, the OGD post-adoption framework is developed and validated. The outcome of this study seeks to guide the OGD implementation in the post-adoption phase in the Malaysian public sector. This study adopted an exploratory sequential mixed-methods design in which the quantitative is the dominant method complement by the qualitative method. The data collection started with semi-structured interviews with four field experts in OGD implementation. Subsequently, combining interviews with government agencies and documents analysis, the initial post-adoption factors of OGD were obtained. The empirical data is collected from 266 government agencies in Malaysia’s public sector using a survey questionnaire. This study employed the Partial Least Square-Structural Equation Modelling (PLS-SEM) as the factor analysis’s primary statistical technique. The statistical analysis indicates that three factors from the organisational context (Culture, Top management support, IT competency), two factors from the technological context (Relative advantage, Complexity), and OGD principles significantly contribute to the OGD implementation in the post-adoption phase. While factors from the environmental context (Incentives, Data demand) and one factor from the technological context (Compatibility) have an insignificant contribution to the OGD implementation in the post-adoption phase. This study contribution is threefold in theoretical, conceptual, and practice. The study contributed theoretically by introducing the post-adoption framework of OGD innovation. Conceptually, this study introduces new factors from the environmental context for OGD post-adoption, namely incentives and data demand. In practicality, this study’s outcome allows policymakers to strategize for sustainable OGD implementation from the data provider’s perspective. The drawback of this research is shown by the survey method, which used a single point of time horizon for data collecting. A longitudinal or case study approach is suggested for future research to understand OGD assimilation in the public sector better.